The examination of family value hierarchies in Russian and Chinese cultures - O. E. Iatsevich; V. V. Iudashkina; L. N. Shabatura; N. A. Tkacheva; A. F. Zakirova (Образование и наука)
Introduction. In the context of globalisation and the intensification of international contacts, there is an increasing need to understand the intercultural differences and similarities between Russian and Chinese youth, particularly in significant areas such as family values. Aim. The present research aimed to identify and analyse the differences and similarities in the perception of family values among students from various cultural contexts. The methodology and research methods. The research methodological framework was grounded in the principles of cultural anthropology, sociology, pedagogy, and psychology, facilitating a multifaceted understanding of the phenomenon under investigation. The study involved 160 students from higher educational institutions in the city of Tyumen, representing both Russian and Chinese cultures. This comprehensive approach incorporated quantitative methods, enabling a visual representation of the cultural features and nuances in the perception of family values and their hierarchy among Chinese and Russian students in Tyumen higher educational institutions. Results. The results indicate that, despite existing cultural differences, Russian and Chinese students demonstrate a similar respect for the institution of family and are committed to preserving family traditions. Scientific novelty. The scientific novelty of this study lies in its reflection of current trends and changes in the perception of family values within the context of cultural exchange, making it significant in the framework of modernity. Practical significance. The practical significance highlights a deeper understanding of intercultural interactions and can serve as a foundation for further sociocultural research in the area of family values.